Green Cellular Demand Control with User-in-the-loop Enabled by Smart Data Pricing using an Effective Quantum (eBit) Tariff - Rainer Schoenen and Hamza Umit Sokun and Halim Yanikomeroglu (2016)
Mobile communications demand for data grows almost two-fold every year and cellular capacity cannot catch up with this in every location and at every point in time. Not only will congestion situations appear more frequently and severely, but also every increase of data transmitted and every new infrastructure point rolled out in order to catch up with that demand is going to consume more total power. One approach towards greener communication is to reduce the actual demand. While technical solutions on Open Systems Interconnection (OSI) layers 1 trough 7 are already being exploited, layer 8, the user, is the original cause of the exploding demand. It is naive to assume that all data is equally important and valuable. User-in-the-loop (UIL) is a paradigm which can exactly hook in at this point, and it suggests to postpone, relocate, abandon or offload less urgent demand by immediate feedback and strong incentives like discounts and penalties in certain situations (in case of congestion). In particular, this means dynamic prices depending on time, location, and congestion (load) status, similar to smart grid for electricity utilities. Accounting and billing with dynamic prices, value-added services, and smart data pricing can be a challenge, and such accounting and billing are utterly incompatible with the flat-rate (all-you-can-consume) concept. However, cellular customers are involuntarily locked into contracts, but it is the current practice in the market, which is not in accordance with the free market spirit. Flat-rate plans are practically dead, but those still luring with this name, while having caps on the maximum allowance, sell fixed-volume packages under a smoother name instead. Ultimately, we need to re-establish usage-based-pricing as a fairer and more favourable way of charging. In this paper we motivate the dynamic pricing of UIL and the upcoming new need for usage-based tariffs. We compare a few status-quo tariff plans with our novel effective quantum (eBit) tariff, which is a usage-based pricing that maps multiple usage dimensions into only one metric, eBits. The eBits will be charged for with one constant unit price dollars/eBit to give the monthly bill. All Quality of Service (QoS)-, application-, and time-dependent dynamic pricing factors are integrated into the effective quantum, so that a user can easily understand his current consumption and the bill upto that point in time. Price differentiation per QoS class is easy with constant scaling factors. %This enables smart data pricing to be easily understood by the consumers. This principle can be extended to any other chargeable metric such as kWh of electricity and m^3 of water. This ultimately enables going greener and training awareness of all consumers.